Pattern and Presentation of Pediatric Spoke Wheel Entrapment Injuries: Our Hospital Experience - Niaz Hussain Keerio, Malik Wasim Ahmed Majoka, Sartaj Lakhani, Hasan Amir Us Saqlain, Syed Abdur Rub Abidi, Altaf Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Finding out how often and how severely kids get their feet caught in the spokes of motorcycle wheels, and what it means for treatment options. Study design: A cross-sectional study Place and Duration: This study was conducted in Ibn-e-Sina University, Muhammad Medical College and Hospital Mirpurkhas from February 2022 to February 2023. Methodology: The study included children who had sustained motorbike spoke wheel injuries after getting their feet entrapped in it. The children were assessed for the severity of the injury as well as the location of the injury. The classification of the injuries was done according to the Tscherne and Oestern classification and graded as 0, I, II, and III. Complete history of the patients was taken followed by a physical examination. After that, relevant investigations were ordered such as radiographs and laboratory investigations. Results: The total number of participants in the present study was 115. The mean age of the participants was 8.62±7.23 years. There were 85 (73.91%) male and 30 (26.09%) female. A total of 78 (67.83%) patients had their right feet injured and 37 (32.17%) patients had their left feet injured. Injury of grade 0 was documented in 17 (14.78%), grade I in 33 (28.69%), grade II in 42 (36.52%) patients, and grade III in 23 (20%) patients. The most common area to get injured in the accident was the heel pad and it was affected in 63 (54.78%) patients. Rupture of the tendon was seen in 11 (9.56%) patients. Fracture of bone was seen in 9 (7.82%) children and only 1 (0.86%) children suffered from neurovascular injury. Conclusion: Injury because of the Motorbike spoke wheel results in different patterns causing multiple levels of damage to tissues and even fractures. Nonetheless, most injuries are related to soft-tissues loss. The most commonly injured area is the heel pad. Phalanges and calcaneus were commonest injured bones. Keywords: Spoke wheel, Motorbike, Fracture, Heel pad, Tscherne and Oestern